2017
DOI: 10.1097/ccm.0000000000002375
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on the Performance of Cardiopulmonary Rescue Teams: A Randomized, Prospective Simulator Study

Abstract: We found important gender differences, with female rescuers showing inferior cardiopulmonary resuscitation performance, which can partially be explained by fewer unsolicited cardiopulmonary resuscitation measures and inferior female leadership. Future education of rescuers should take gender differences into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 29 publications
2
52
3
2
Order By: Relevance
“…Similarly, another study assessed the influence of gender on leadership in fourth‐year medical students using high‐fidelity simulation. This study found that female gender was associated with a lower number of “secure leadership statements” (defined as strong and direct statements, rather than statements formulated as a question) . Furthermore, female residents often experience the added stress of needing to negotiate relationships with nurses and “gain their trust” or to “earn” their position as resuscitation leader …”
mentioning
confidence: 93%
“…Similarly, another study assessed the influence of gender on leadership in fourth‐year medical students using high‐fidelity simulation. This study found that female gender was associated with a lower number of “secure leadership statements” (defined as strong and direct statements, rather than statements formulated as a question) . Furthermore, female residents often experience the added stress of needing to negotiate relationships with nurses and “gain their trust” or to “earn” their position as resuscitation leader …”
mentioning
confidence: 93%
“…43 Other studies have reported lower evaluation scores for women anesthesia trainees during their critical care rotations 44 ; and inferior cardiopulmonary resuscitation performance in women. 45 Failure to show stereotypical leadership characteristics may explain the perception of lower performance in women, particularly in specialties such as emergency medicine that expect traditionally maledefined behaviors (e.g., independence, assertiveness). 43,45 Paradoxically, women who assume such leadership characteristics may be penalized for their behaviour.…”
Section: Support Women Traineesmentioning
confidence: 99%
“…45 Failure to show stereotypical leadership characteristics may explain the perception of lower performance in women, particularly in specialties such as emergency medicine that expect traditionally maledefined behaviors (e.g., independence, assertiveness). 43,45 Paradoxically, women who assume such leadership characteristics may be penalized for their behaviour. 46,47 For both women and men trainees, anticipating and adhering to gendered behavioral expectations is stressful and distracts from clinical work.…”
Section: Support Women Traineesmentioning
confidence: 99%
“…10 A recent simulation study found that women-only cardiopulmonary rescue teams had significantly less 'hands-on' time and more delays in beginning chest compressions compared with men-only teams. 11 Within teams of both men and women, women rescuers issued fewer leadership statements and engaged in fewer unsolicited cardiopulmonary rescue measures. However, new research suggests that gender diversity may actually increase cooperation among OR teams.…”
Section: Defining Sex and Gendermentioning
confidence: 99%